Determinants of Sustainable MSME Involvement in The MICE Business: Evidence from Yogyakarta - Nining Yuniati; Aditha Agung Prakoso; Susilo Susilo (E-Journal of Tourism, 2026)
Meeting Incentive Conference and Exhibition (MICE) is one of the proud sectors of the tourism business for many destinations in Indonesia. Its ability to support the economy, particularly in absorbing labor through MSME, is the main reason MICE is a prioritized business. There are many factors that significantly impact the sustainability of the MICE business, involving organizers (EOs), suppliers (vendors), and project owners (government/private sector). This research aims to identify a number of factors that influence the sustainability of the MICE industry. Data observation was conducted using a sequential mixed method. In the qualitative data observation processed with NVIVO, 5 variables were successfully identified as theoretical constructs influencing the sustainability of the MICE business: Commitment; Product Innovation; Product Capacity; Product Quality & Control; Time, as well as one moderating variable: Payment. The payment variable plays an important role in supporting the provision and operation of Product Capacity, Product Quality & Control, and Time. On the quantitative data, those variables were then tested on 147 MICE practitioners consisting of organizers and suppliers using PLS-SEM to prove the validity of their influence on the sustainability of their businesses. Detailed discussions are presented further in this paper.